2018
DOI: 10.3389/fpsyg.2018.00042
|View full text |Cite
|
Sign up to set email alerts
|

Sociality Mental Modes Modulate the Processing of Advice-Giving: An Event-Related Potentials Study

Abstract: People have different motivations to get along with others in different sociality mental modes (i.e., communal mode and market mode), which might affect social decision-making. The present study examined how these two types of sociality mental modes affect the processing of advice-giving using the event-related potentials (ERPs). After primed with the communal mode and market mode, participants were instructed to decide whether or not give an advice (profitable or damnous) to a stranger without any feedback. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Skills training in these areas is a vital component of several established treatment methods directed to individuals with emotion regulation difficulties and subsequent disruptive behaviors, such as dialectical behavior therapy ( McCann et al, 2000 ; Brown et al, 2013 ) or emotion regulation group therapy ( Gratz and Gunderson, 2006 ; Gratz and Tull, 2011 ). Recently, the concept of eHealth has gained increasing support in forensic psychiatry ( Kip et al, 2018 ), where developments in virtual reality technology for skills training (e.g., aggression management; Tuente et al, 2018 ; Klein Tuente et al, 2020 ) have been especially promising. However, while these could provide completely new arenas for skills training in emotion and behavior regulation for forensic psychiatric patients, there remains a great need for research on effective treatment components.…”
Section: Discussionmentioning
confidence: 99%
“…Skills training in these areas is a vital component of several established treatment methods directed to individuals with emotion regulation difficulties and subsequent disruptive behaviors, such as dialectical behavior therapy ( McCann et al, 2000 ; Brown et al, 2013 ) or emotion regulation group therapy ( Gratz and Gunderson, 2006 ; Gratz and Tull, 2011 ). Recently, the concept of eHealth has gained increasing support in forensic psychiatry ( Kip et al, 2018 ), where developments in virtual reality technology for skills training (e.g., aggression management; Tuente et al, 2018 ; Klein Tuente et al, 2020 ) have been especially promising. However, while these could provide completely new arenas for skills training in emotion and behavior regulation for forensic psychiatric patients, there remains a great need for research on effective treatment components.…”
Section: Discussionmentioning
confidence: 99%
“…Preferences motivate interpersonal behavior (Jeung et al., 2016). Previous evidence has shown that interpersonal behavior involving material rewards, especially monetary payoffs, is market‐oriented (Distefano et al., 2018; Heyman & Ariely, 2004; Li et al., 2020; Li et al., 2018). Specifically, interpersonal behavior involving monetary payoffs conjures up the market pricing mode , which is a fundamental behavioral mode of relating to others socially (Caruso et al., 2013; Fiske, 1992; Gasiorowska & Zaleskiewicz, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, interpersonal behavior involving monetary payoffs conjures up the market pricing mode , which is a fundamental behavioral mode of relating to others socially (Caruso et al., 2013; Fiske, 1992; Gasiorowska & Zaleskiewicz, 2020). The market pricing mode underlies the costs and benefits trade‐off analyses, in that a person is likely to focus on what he/she will receive in exchange equally before enacting a given behavior (Heyman & Ariely, 2004; Li et al., 2020; Li et al., 2018). Therefore, when engaging in actions involving monetary payoffs, individuals have a relatively stronger preference for reciprocity (Caruso et al., 2017; Cox & Deck, 2005; Vohs et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Eye gaze and money are important social cues to prime sociality mental modes, which are closely related to reputation and benefit (Li et al, 2018). Many studies have shown that public behavior can bring people a good reputation and improve the social status of the helper in the group (Anderson & Kilduff, 2009;Willer, 2009).…”
Section: Introductionmentioning
confidence: 99%